Allergic rhinitis self-care advice in community pharmacies: A simulated patient study - Rian Lelie - van der Zande; Ellen S. Koster; Martina Teichert; Marcel L. Bouvy (Elsevier, 2021)
Background: Pharmacists and pharmacy assistants can support consumers by identifying minor ailments and providing evidence-based advice about treatment options. In the Netherlands, advice is based on national minor ailment guidelines and structured WWHAM questions (Who, What, How long, Action, Medication). Objectives: To study whether pharmacy assistants provide guideline-compliant advice for allergic rhinitis based on WWHAM and condition-specific questions (When and Familiarity) and their association with appropriate self-care advice. Methods: A retrospective study of the assessments of simulated patient (SP) visits regarding one condition- and two symptom-based cases of allergic rhinitis in Dutch community pharmacies. Pharmacies that participated in 2014, 2016 and 2018 were selected. SPs documented their observations of the problem analysis, dispensing and client interaction on a standardized scoresheet. Dispensing of an oral antihistamine according to the guideline recommendation was considered as the correct outcome. Chi-square tests were used to analyze differences in scores for problem analysis of pharmacies with correct and incorrect advice provision in 2014 and 2018. Predictors for correct outcome were identified by univariate and multivariate logistic regression analysis. Results: Data from 673 pharmacies were available for all three years. In 2014 and 2018, problems were presented as a symptom (running nose), and 41.2% and 21.1% of pharmacies dispensed an antihistamine. For the condition-based problem (allergy) in 2016, 96.0% of participating pharmacies dispensed an antihistamine. Both in 2014 and 2018, each additional problem analysis question increased the odds ratio of providing correct advice. Questions asked about 'hay fever symptoms', 'medication', 'when symptoms occurred', and 'familiar symptoms' were significant predictors of correct advice provision. Conclusions: Most pharmacies provided appropriate advice for a condition-based request but less than half of them provided appropriate advice for a symptom-based request. More questions asked was associated with an increased chance of providing correct advice. Addition of condition-specific questions may improve the WWHAM-method.